2017
DOI: 10.1194/jlr.p078816
|View full text |Cite
|
Sign up to set email alerts
|

LDL cholesterol level in fifth-grade schoolchildren associates with stature

Abstract: Short stature is associated with increased LDL-cholesterol levels and coronary artery disease in adults. We investigated the relationship of stature to LDL levels in children in the West Virginia Coronary Artery Risk Detection in Appalachian Communities (CARDIAC) Project to determine whether the genetically determined inverse relationship observed in adults would be evident in fifth graders. A cross-sectional survey of schoolchildren was assessed for cardiovascular risk factors. Data collected at school screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
(18 reference statements)
1
14
0
Order By: Relevance
“…In Korea, the overall prevalence of dyslipidemia in adolescents aged 10–18 years is 21.7~25.2%; prevalence is reported to be two times higher (53.1~56.1%) in obese adolescents 9 . However, few studies have been conducted on the relationship between height and blood lipid concentrations in children and adolescents 1015 . Specifically, there have been no studies on the association of dyslipidemia and height in Korean adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the overall prevalence of dyslipidemia in adolescents aged 10–18 years is 21.7~25.2%; prevalence is reported to be two times higher (53.1~56.1%) in obese adolescents 9 . However, few studies have been conducted on the relationship between height and blood lipid concentrations in children and adolescents 1015 . Specifically, there have been no studies on the association of dyslipidemia and height in Korean adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, serum lipid levels and BMI in childhood correlate strongly with these values in middle age [43]. The correlation between short stature and elevated plasma LDL-C levels has also been observed in school children in fifth grade [11], however, we did not find an association between LDL-C and height, which may be because the study subjects with a height SDS of no more than − 2 were limited.…”
Section: Discussionmentioning
confidence: 59%
“…Endocrinologists have paid considerable attention to screening lipid profiles and have demonstrated the related factors in youths, especially in obese children, who are prone to having unfavourable lipid profiles [57]. Some studies have provided evidence that short stature is a risk factor associated with CHD [8, 9] and non-high-density lipoprotein (non-HDL) cholesterol levels even after adjustment for body mass index (BMI) in adults [10], and recent studies have reported that an inverse relationship between height and non-HDL cholesterol is also exists in children [1113]. Therefore, these studies suggest the need to analyse the lipid profiles and the associated factors, especially in children and adolescents with short stature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prospective large-scale studies and meta-analyses have reported that there is an inverse association between height and cardiovascular disease (CVD) risk [3][4][5][6] . Dyslipidaemia is one of the main risk factors for CVD, and there is a negative association between height and lipid pro le in children and adults [7][8][9] . Hence, it is necessary to pay attention to the lipid pro le of children with short stature, which is a risk factor for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%